Lewis Kirk Brown papers - Brown, Lewis Kirk, 1843-1926.
Letters (1863 August 1, 11, 15) from Walt Whitman to Brown relating to the progress of the Civil War, conditions in Washington, D.C., and various personal matters. Includes two typescripts relating to the letters and to the friendship between Brown and Whitman. Also includes a letter (10 April 1916) from Brown to J.E. Boos describing Brown's encounters with Abraham Lincoln and a biographical sketch of Brown.
Union soldier.
Collection material in English.
The 1927 gift described in: Walt Whitman : a guide based upon the collections of the Library of Congress. Washington, D.C. : 1955.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Boos, J. E. -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Whitman, Walt, -- 1819-1892 -- Correspondence; United States -- History -- Civil War, 1861-1865.; Washington (D.C.) -- History -- Civil War, 1861-1865.; Soldiers